Self-Compassion dan Negative Emotional States Pada Mahasiswa Kedokteran Umum: Hubungan dan Prevalensi - Anindhita Parasdyapawitra Amaranggani; Thalia Tresnaning Prana; Ni Made Cintya Dwiyanti Arsari; Agung Maulana Surbakti; Amalia Rahmandani (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
Negative emotional states, such as depression, anxiety, and stress, can arise and impact the individual's adaptive function. Self-compassion includes treating oneself with wisdom and understanding when faced with suffering, which helps improve self-regulation in dealing with emotional problems. This study aims to see the relationship between self-compassion and negative emotional states in Diponegoro University medical students, involving 118 participants of second-year students using the convenience sampling technique. Measurements in the study were carried out using the self-compassion scale (22 items, Î± = 0.925) and the DASS-21 Indonesian version (21 items, Î± = 0.892). Spearman's rho showed a significant negative relationship between self-compassion and negative emotional states (rxy = -0.630, p = 0.000). Self-compassion was also found to have a significant negative relationship with depression (rxy = -0.643, p = 0.000), anxiety (rxy = -0.440, p = 0.000), and stress (rxy = -0.516, p = 0.000). These results indicate that the higher self-compassion of the participants, the lower the negative emotional states, and vice versa. Self-compassion predicts negative emotional states in participants ranging from depression, stress, and anxiety sequentially. The further identified prevalence of negative emotional states in participants in this study. A program to enhance self-compassion is needed to reduce negative emotional states.